UPAYA PENINGKATAN KESIAPSIAGAAN MASYARAKAT TERHADAP BENCANA GEMPA BUMI DAN TSUNAMI DI INDONESIA : LITERATUR RIVIEW - Ohorella, Usman Barus; Tantri, Kaliana; Imran, Andi Miftahul Khair; Achmad, Irhamdi; Metekohy, Feby Adolf (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2024)
Background: Disaster preparedness is something that all people in Indonesia should have. Because various kinds of disasters are threats that can claim lives, property, and public facilities. Purpose: This systematical review was created to be able to provide information regarding community preparedness and the methods used to improve it. Method: Systematical Review. Search data sources use Google Scholar and PubMed, articles on topics published in Indonesian and English from 2018-2023. Results: The results of the literature review obtained 10 articles that match the inclusion criteria which provide the results of various methods provided to increase disaster preparedness including disaster counseling, leaflets/booklets, simulations, etc. Conclusion: various methods can be given as an effort to increase community preparedness. Recommendation: Providing education must continue to be carried out to train community preparedness for earthquake and tsunami disasters.